Fermentation profile, nutritional value and aerobic stability of mixed elephant grass and butterfly pea silages - Crislane de Souza Silva; Aicanã Santos de Miranda; Judicael Janderson da Silva Novaes; Cleyton de Almeida Araújo; Amélia de Macedo; Janiele Santos de Araújo; Deneson Oliveira Lima; João Virgínio Emerenciano Neto; Glayciane Costa Gois; Gherman Garcia Leal de Araújo; Fleming Sena Campos (Ciência Animal Brasileira, 2024)
The aim was to evaluate the effect of butterfly pea inclusion on the fermentation dynamics, nutritional quality and aerobic stability of mixed elephant grass silages. Butterfly pea levels (0, 20, 40, 60 and 80% on a natural matter basis) were added to elephant grass silages. A completely randomized design was adopted, with 5 treatments and 3 replications, totaling 15 experimental silos, which were opened after 30 days of fermentation. The inclusion of butterfly pea in elephant grass silages resulted in a quadratic effect for permeability, density, maximum pH, final pH, time to reach maximum temperature and aerobic stability (P<0.05). Butterfly pea inclusion levels increased dry matter recovery, pH, dry matter, organic matter, ether extract, crude protein and total digestible nutrients (P<0.001) and reduced gas and effluent losses, mineral matter, neutral detergent fiber, acid detergent fiber, hemicellulose, cellulose, lignin and total carbohydrates (P<0.001). Inclusions of 40, 60 and 80% of butterfly pea provided temperature increases at 10, 20, 30 and 40 hours. The inclusion of butterfly pea with levels of up to 80% reduces fermentation losses, allows for a nutritional increase and increase in aerobic stability of silages.